The Effect of Melatonin on Locomotor Behavior and Muscle Physiology in the Sea Cucumber Apostichopus japonicus - Ding, Kui; Zhang, Libin; Zhang, Tao; Yang, Hongsheng; Brinkman, Richard (Frontiers in Physiology, 2019)
Melatonin is a highly conserved hormone in evolutionary history. It occurs in numerous organisms and plays a role in the endocrine and immune systems. Locomotor behavior is a basic behavior in animals and is an important indicator of circadian rhythms, which are coordinated by the nervous and endocrine systems. To date, the effect of melatonin on locomotor behavior has been studied in vertebrates, including Syrian hamsters, sparrows, rats, zebrafish, goldfish and flatworms. However, there have been few studies of the effects of melatonin on locomotor behavior in marine invertebrates. The goals of present study were to show the existence of melatonin in the sea cucumber Apostichopus japonicus and to evaluate its effect on locomotor activity. In addition, muscle tissues from control and melatonin-treated sea cucumbers were tested using ultra performance liquid chromatography and quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) to determine the changes of metabolic activity in muscle. Melatonin was present in the coelomic fluid of A. japonicus at a concentration of ~135.0 ng/L. The total distance travelled and number steps taken over nine hours after melatonin administration decreased with increasing concentration of the melatonin dose. Mean and maximum velocity of movement and stride length and stride frequency also decreased, but their differences were not statistically significant. Overall, these results suggest that melatonin administration had a sedative effect on A. japonicus. The levels of 22 different metabolites were altered in the muscle tissues of melatonin-treated sea cucumbers. Serotonin, 9-cis retinoic acid, all-trans retinoic acid, flavin mononucleotide in muscles were downregulated after melatonin administration. Moreover, a high free fatty acid (FFA) concentration and a decrease in the adenosine 5’-triphosphate (ATP) concentration in the muscle tissues of the melatonin-treated group were detected as well. These results suggest that the sedative effect of melatonin involves some other metabolic pathways, and the reduced locomotor modulator—serotonin, inhibited fatty acid oxidation and disturbed oxidative phosphorylation are potential physiological mechanisms that result in the inhibitory effect of melatonin on locomotion in sea cucumbers.